(3aJM GdbQjH GdeLjH Ydi GdJQZjH hGdJQgjHs - (3MSf Hf YdjGdajhej GdbGgQj, CHh Ydj,J (B870 (3g` s
(3ChdgG (B:s
(3cJGH GdCOH hZjQg GdJQZjH ai GdMjGA heG LGA ai aVdg Ef QShd Gddg Udi Gddg Ydjg hSde eQ Ydi QLd ef GdCfUGQ hgh jZX CNGg ai GdMjGA GdMOjK s
(3BNQgG (B:s
(3jfJgi HGdJQZjH ai GdQLGA hMSf GdXf HGdGSjeG YfO GdehJ Hbhdg (B: (3bhdg ai GdMOjK bGd Gddg YR hLd CfG YfO Xf YHOi Hi Ef Xf NjQkG adg hEf Xf TQkG adg GdMOjK adjXf Hi eG TGA s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdMOjK h GdeUWdMs